DETERMINATION OF SUITABILITY OF DEOILED CAKES OF NEEM AND JATROPHA FOR MASS MULTIPLICATION OF PSEUDOMONAS FLUORESCENS - AJAY TOMER; RAMJI SINGH; MANOJ KUMAR MAURYA (The Bioscan, 2014)
Jatropha cake was found to be best substrate for supporting the highest population dynamics and longevity of P. flourescens in vitro. Both these cakes supported the population of P. flourescens up to 120 days at 28±2ºC. Highest population (271.00×10x ) of P. flourescens was noticed on Jatropha cake after 45 days of inoculation and incubation at 28±2ºC when maintained with 15% moisture, while on Neem cake, highest population (208.00×10x ) of P. flourescenswas noticed after 60 days of inoculation when maintained with 25% moisture. Jatropha cake was better than Neem cake for supporting population and longer shelf life of P. flourescens in vitro. Result of this study may help for using deoiled cakes of different TBOs (tree born oil seeds) in mass multiplication of different bio-agents specially P. flourescens.